To find the solution to the system of linear equations \( y = 3x + 1 \) and \( y = -2x - 4 \), we need to determine which point satisfies both equations.
Let's check each of the given points:
-
Point \((-1, -2)\):
- For \( y = 3x + 1 \): \( y = 3(-1) + 1 = -3 + 1 = -2 \) → True.
- For \( y = -2x - 4 \): \( y = -2(-1) - 4 = 2 - 4 = -2 \) → True.
- This point satisfies both equations.
-
Point \((0, -4)\):
- For \( y = 3x + 1 \): \( y = 3(0) + 1 = 0 + 1 = 1 \) → False.
- This point does not satisfy the first equation.
-
Point \((0, 1)\):
- For \( y = 3x + 1 \): \( y = 3(0) + 1 = 0 + 1 = 1 \) → True.
- For \( y = -2x - 4 \): \( y = -2(0) - 4 = 0 - 4 = -4 \) → False.
- This point does not satisfy the second equation.
-
Point \((-2, 3)\):
- For \( y = 3x + 1 \): \( y = 3(-2) + 1 = -6 + 1 = -5 \) → False.
- This point does not satisfy the first equation.
Based on the evaluations, the only point that satisfies both equations is \((-1, -2)\).
Thus, the correct answer is:
\((-1, -2)\)